The Image of the Land and Its Functions in Tolstoy’s Novel Resurrection - Valeria G. Andreeva (Studia Litterarum, 2020)
The paper argues that Leo Tolstoy uses the national disaster paradigm represented in the epic novel War and Peace to depict the relatively peaceful time in his novel Resurrection as he raises the question of the growing crisis in Russia and the problem of the survival of Russian people. One of the central images of this latter novel is the image of the land. Its function is to support a system of Tolstoy’s antitheses that in his late period, aimed not only to rebuke the existing order but also to create a large-scale image of national unity. The image of the land in Resurrection ties together thematic and ideological strata of the novel that manifest its epic features. I argue that although Tolstoy abandoned his initial intention to make the acute social and political landrelated issue the center of his work, the motif nevertheless remains relevant. The image of the land is ciphered in the description of the severity of prisoners’ life and Nekhlyudov’s attempts to help the prisoners. Moreover, it is closely connected with all spheres of Russian life, it is a marker of Nekhlyudov’s spiritual growth that allows not only place the character’s “resurrection” within specific realities of historical time, but also presents it in the traditions of Christian anthropology. The image of the land allots the novel with trans-historical meaning and contributes to the implementation of the religious consciousness in Tolstoy’s work.